1983
DOI: 10.1148/radiology.147.1.6338564
|View full text |Cite
|
Sign up to set email alerts
|

Work in progress: a correction for tissue iodine accumulation in videodensitometric measurements of left ventricular ejection fraction.

Abstract: Left ventricular ejection fractions were determined following eight intravenous injections in three dogs using area/length and digital videodensitometric techniques. Ejection fractions were measured by both techniques for all beats during left ventricular opacification. Even after noniodinated background corrections, tissue iodine accumulation produced large errors in measured iodine content late in the contrast material curve. By using a model for tissue iodine accumulation, an algorithm was developed that ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As discussed earlier [3,9,11,12,13] there are several further problems when the density of X-ray images is evaluated quantitatively. Four main sources of errors can be distinguished: cyclic density fluctuations modifying the contrast wash-out curve, accumulation of iodine in tissue superposing the ventricular region, image degradation due to scatter radiation and veiling glare, and data scattering due to physiologic beat-to-beat variations, motion artifacts, and inhomogeneous indicator mixing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed earlier [3,9,11,12,13] there are several further problems when the density of X-ray images is evaluated quantitatively. Four main sources of errors can be distinguished: cyclic density fluctuations modifying the contrast wash-out curve, accumulation of iodine in tissue superposing the ventricular region, image degradation due to scatter radiation and veiling glare, and data scattering due to physiologic beat-to-beat variations, motion artifacts, and inhomogeneous indicator mixing.…”
Section: Discussionmentioning
confidence: 99%
“…i upper panel). Proposed solutions to this problem are to approximate that rise functionally [3,12,13] or to record it with the aid of a region next to the ventricle [4,5,8]. We found that the application of the method of differences introduced for the determination of FEF for analog densitometry by Falliner and coworkers [11] was both simple and reliable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation